Aplikasi Pemantauan Kesehatan Pada Lansia Resiko Tinggi Menggunakan Algoritma Genetika Berbasis Smartphone Android Di Rumah Sakit Cut Mutia Lhokseumawe - Rizki Setiawan; angga pratama; Ananda Faridhatul Ulva (Jurnal Tika, 2022)
Health is the most important thing that must always be considered because if health deteriorates then every activity will definitely be difficult to do, but not infrequently due to some conditions we have to fall sick and even have to get intensive care so that it requires further supervision from the hospital or hospital. Puskesmas, especially for elderly family members who require special care and attention. Health monitoring applications in the elderly provide convenience for families in caring for the health of family members who are elderly and also make it easier for the hospital to see progress data from patients. This research is in the stage of making the availability of real-time monitoring features from the puskesmas or hospital in the future and some features are available and there are some real-time medical record features so that the hospital can find out the health history of the patient in real time. The purpose of this research is to implement and build an application for Health Monitoring in the Elderly at High Risk with an Android-Based Genetic Algorithm. then apply the genetic algorithm method in determining health in high-risk elderly. The menu on the application includes patient data, consultation page, examination results page, doctor data, patient data, type of disease, medical records, handling, complaints page, patient profile page, healthy food page. Furthermore, it makes it easier for families and hospitals to treat patients because there are medical record features and Android-based high-risk elderly patient monitoring features. Then the results of this study are smartphone-based health application technology for health surveillance applications in the elderly based on Android. The last is to make it easier for family members and the puskesmas in conducting health surveillance of the elderly